RETRACTED: Survivin knockdown alleviates pathological hydrostatic pressure-induced bladder smooth muscle cell dysfunction and BOO-induced bladder remodeling via autophagy - Chen, Guo; Chen, Shuang; Di, Xingpeng; He, Shengyin; Liu, Yugao; Qu, Rui; Luo, Yi; Liu, Yuebai; Yang, Luo (Frontiers in Cell and Developmental Biology, 2022)
Aim: Bladder outlet obstruction (BOO) leads to bladder wall remodeling accompanying the progression from inflammation to fibrosis where pathological hydrostatic pressure(HP)-induced alteration of bladder smooth muscle cells(BSMCs) hypertrophic and excessive extracellular matrix(ECM) deposition play a pivotal role. Recently, we have predicted survivin(BIRC5) as a potential hub gene that might be critical during bladder fibrosis by bioinformatics analyses from rat BOO bladder, but its function during BOO progression remains unknown. Here, we investigated the role of survivin protein on bladder dysfunction of BOO both in vitro and in vivo. Methods: Sprague-Dawley female rats were divided into three groups: control group, BOO group, and BOO followed by the treatment with YM155 group. Bladder morphology and function were evaluated by Masson staining and urodynamic testing. To elucidate the underlying mechanism, hBSMCs were subjected to pathological HP of 200 cmH2O and co-cultured with the presence or absence of survivin siRNA and/or autophagy inhibitor 3-MA. Autophagy was evaluated by the detection of Beclin1 and LC3B-II expression, proliferation was conducted by the EdU analysis and PCNA expression, and fibrosis was assessed by the examination of Col 1 and Fn expression. Results: BOO led to a gradual alteration of hypertrophy and fibrosis of the bladder, and subsequently induced bladder dysfunction accompanied by increased survivin expression, while these histological and function changes were attenuated by the treatment with YM155. HP significantly increased survivin expression, upregulated Col1 and Fn expression, enhanced proliferation, and downregulated autophagy markers, but these changes were partially abolished by survivin siRNA treatment, which was consistent with the results of the BOO rat experiment. In addition, the anti-fibrotic and anti-proliferative effects of the survivin siRNA treatment on hBSMCs were diminished after the inhibition of autophagy by the treatment with 3-MA. Conclusion: In summary, the upregulation of survivin increased cell proliferation and fibrotic protein expression of hBSMC and drove the onset of bladder remodeling through autophagy during BOO. Targeting survivin in pathological hBSMCs could be a promising way to anti-fibrotic therapeutic approach in bladder remodeling secondary to BOO.